Pengelolaan Zakat dalam Memberdayakan Masyarakat Miskin pada Badan Amil Zakat Nasional Kabupaten Tuban - Risa Yulianti; R. Zainul Mushthofa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Good and correct management carried out by BAZNAS can be carried out with many programs with various objectives. One of them is to empower the poor. The role of BAZNAS here, besides distributing it, also provides direction so that the funds received are more useful. Seeing the high amount of zakat, infaq, shodaqoh funds collected at BAZNAS Tuban Regency, and one of the missions of BAZNAS Tuban Regency is to empower the poor who are still in their productive age. Zakat management in empowering the poor at BAZNAS Tuban district as well as the inhibiting and supporting factors that occur in the management of zakat. With the aim of being able to answer and describe, and analyze the management of zakat in empowering the poor at BAZNAS Tuban Regency. Zakat as an economic element plays an important role in shaping the fiscal aspect of a country's economic structure. Zakat is worship maaliyah ijtima'iyyah which means material social and has a strategic function. In accordance with the nature of zakat obligations that must be carried out with certainty, then even in handling zakat must be managed properly by the relevant institutions. At the end of the twentieth century, along with the revival of the Islamic community in various sectors of life, the teachings of zakat have also become one of the sectors that have begun to be explored. Indonesia is no exception. The management of zakat in this period still involved the Regional Government through the inclusion of the Regional Secretary and the Head of the Public Welfare Section of the Regional Secretariat of Tuban Regency in the Executive element. This is because BAZNAS of Tuban Regency as a non-structural government institution must still be able to synergize with the Regional Government with the aim of optimizing revenues and efforts to assist the Regional Government in reducing the poverty rate in Tuban Regency through zakat, infaq and almsgiving funds.